PENGARUH PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN - Eka Saputra, I Gede Ade; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
Human resource management in the organization is not easy, as it involves various elements within the organization are employees, leaders and the system itself. However it is known that there is a problem within the company that is the high level of employee dissatisfaction is caused by a lack of attention and good communication from the leader. This study aimed to examine the effect of leadership style and organizational culture on employee job satisfaction. This research was conducted at Slippery Stone Greek Restaurant and Bar. Sampling of this research is the method of saturated samples. Data were collected using survey method with interviews and questionnaires. The respondents of this research were 62 employees. Data analysis techniques used in this research is multiple linear regression analysis. These results indicate that leadership style has a positive effect on employee job satisfaction, and organizational culture has a positive effect on job satisfaction.